2018
DOI: 10.1016/j.stemcr.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Generation of TCR-Expressing Innate Lymphoid-like Helper Cells that Induce Cytotoxic T Cell-Mediated Anti-leukemic Cell Response

Abstract: SummaryCD4+ T helper (Th) cell activation is essential for inducing cytotoxic T lymphocyte (CTL) responses against malignancy. We reprogrammed a Th clone specific for chronic myelogenous leukemia (CML)-derived b3a2 peptide to pluripotency and re-differentiated the cells into original TCR-expressing T-lineage cells (iPS-T cells) with gene expression patterns resembling those of group 1 innate lymphoid cells. CD4 gene transduction into iPS-T cells enhanced b3a2 peptide-specific responses via b3a2 peptide-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Although the aforementioned studies show the potential of iPSCderived T cells as an alternative cell source for T cell immunotherapy, recent studies, including those at our laboratory, revealed that T cells differentiated from iPSCs using the current differentiation methods display features similar to γδT cells or innate lymphoid cells. [30][31][32] Current differentiation culture induces T cells expressing CD56, a marker for natural killer cells, during multiple rounds of expansion. General schema illustrating autologous T cell manufacturing.…”
Section: Plurip Otent S Tem Cell S a S True "Off-the-s Helf" T Cellmentioning
confidence: 99%
“…Although the aforementioned studies show the potential of iPSCderived T cells as an alternative cell source for T cell immunotherapy, recent studies, including those at our laboratory, revealed that T cells differentiated from iPSCs using the current differentiation methods display features similar to γδT cells or innate lymphoid cells. [30][31][32] Current differentiation culture induces T cells expressing CD56, a marker for natural killer cells, during multiple rounds of expansion. General schema illustrating autologous T cell manufacturing.…”
Section: Plurip Otent S Tem Cell S a S True "Off-the-s Helf" T Cellmentioning
confidence: 99%
“…Previous studies have shown that HECs or HPCs differentiated from ESCs or iPSCs could be induced to differentiate into the T-cell lineage by co-culturing with OP9 feeder layer-expressing notch ligands, DL1 or DL4, with a limited efficiency of αβ- or γδ-TCR + cell generation 2 , 3 , 32 . It has been also demonstrated that generation of iPSC from T-cells (T-iPSCs) and redifferentiation enhance the efficiency of αβTCR-expressing cell generation from iPSCs 4 7 , 33 , 34 . Recently, we have also shown that exogenous TCR transduction in clinical-grade iPSCs can be used as a starting material to generate antigen-specific TCR-engineered iCD8αβ + T-cells with in vivo activity, thereby minimizing inter-clonal variations of iPSCs and bypassing laborious iPSC generation processes 9 .…”
Section: Discussionmentioning
confidence: 99%
“…PBMC samples were obtained from healthy volunteers who provided written informed consent. The H25-4, H25-31, and GPC3#16-1 iPSC clones were generated from CTL clones by Sendai virus reprogramming vectors as previously described 4 , 9 , 33 , 34 . An HLA homozygous iPSC line FfI01s04 was established in CiRA and distributed with informed consent and permission of the Ethical Review Board at CiRA.…”
Section: Methodsmentioning
confidence: 99%
“…iPSCs represent a potential immune cell source for cancer immunotherapy (Sachamitr et al, 2014). However, despite their ability to differentiate into various somatic cell types, a largescale cell culture system, extensive labor, and long periods for cell differentiation are required to generate sufficient immune cells from iPSCs (Kitayama et al, 2016;Senju et al, 2009;Ueda et al, 2018). We previously developed a simple and efficient method for obtaining numerous myeloid cells from human and mouse iPSCs (Haruta et al, 2013;Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%